2023
DOI: 10.2147/prbm.s284645
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Verbal Fluency in Alzheimer’s Disease: Evidence to Date

Abstract: Since their development, verbal fluency tests (VFTs) have been used extensively throughout research and in clinical settings to assess a variety of cognitive functions in diverse populations. In Alzheimer’s disease (AD), these tasks have proven particularly valuable in identifying the earliest forms of cognitive decline in semantic processing and have been shown to relate specifically to brain regions associated with the initial stages of pathological change. In recent years, researchers have developed more nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 129 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…The two studies evaluating language found a positive association with PNS activity [66,73]. This is consonant with the sparse cross-sectional literature (e.g., [121,122]), and unsurprising since the category fluency and Mill Hill tests also rely upon executive control [83][84][85]123]. To better clarify the association between HRV and language, it could be useful to employ language tests, like the Boston Naming Test, that would seem to be less dependent on executive functioning [124].…”
Section: Languagementioning
confidence: 69%
See 1 more Smart Citation
“…The two studies evaluating language found a positive association with PNS activity [66,73]. This is consonant with the sparse cross-sectional literature (e.g., [121,122]), and unsurprising since the category fluency and Mill Hill tests also rely upon executive control [83][84][85]123]. To better clarify the association between HRV and language, it could be useful to employ language tests, like the Boston Naming Test, that would seem to be less dependent on executive functioning [124].…”
Section: Languagementioning
confidence: 69%
“…Two studies [ 69 , 74 ] computed composite test scores for episodic memory and executive functioning. The cognitive tests used to evaluate global and domain-specific cognition are shown in Table 2 and are in accordance with the standard neuropsychological literature [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. As can be seen, the two language tests also gauged executive functioning due to the close relationship between these two domains [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of reduced category fluency but not letter fluency performance in MCI progressors relative to nonprogressors thus points to the underlying semantic nature of the deficit. It is also worth noting that other methods, such as a phonemic/category discrepancy score, have proven useful in distinguishing semantic from executive components of verbal fluency (Marra et al, 2021; Wright et al, 2023b), and may be more operational in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cognitive problems caused by dementia, verbal and speech impairments can be easily observed. Therefore, verbal fluency features can serve as a promising diagnostic biomarker 7 .…”
Section: Introductionmentioning
confidence: 99%